THE NEED AND RATIONALE OF THYROID FUNCTION TESTS IN A TERTIARY CARE LABORATORY - Azim, Waqar; Shafi, Mohsin; Farooq, Wajiha; Azim, Saad; Kiyani, Khalid Amjad (Journal of Postgraduate Medical Institute, 2011)
Objective: To find out the outcome of thyroid function tests in a tertiary care laboratory and to assess the Methodology: It was a descriptive study which was carried out in a tertiary care laboratory of Rawalpindi. Patient's demographic data and clinical details were recorded. Blood samples were obtained and analysis was done. Results were analyzed on SPSS version 17. Results : One hundred twenty seven samples of both sexes with age range 15-80 years were selected for study and non probability random sampling was done. There were 94 (74%) females and 33 (26%) males. Age range of the patients was 38.8 + 14.4 years. Majority of the patients were found to be euthyroid 76.38%. On basis of history, the most common symptom for which thyroid testing was advised was lethargy. Conclusion : For non-specific symptoms, full thyroid profile should not be advised, rather Thyroid Stimulating Hormone (TSH) should be used as a first line screening test. Full thyroid profile is an expensive test and has financial implications on both patients as well as the laboratory, so rational use of thyroid function tests is recommended. rationality of thyroid function tests advice.